2011
DOI: 10.1002/kin.20609
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional versus conventional application of pseudo‐first‐order kinetics to fundamental organic reactions

Abstract: Three new analysis procedures for pseudo-first-order kinetics are introduced and applied to eight different fundamental organic reactions. The reactions belong to the following classes: nitroalkane proton transfer, formal hydride ion transfers from NADH model compounds, and S N 2 reactions of alkyl halides with ionic and neutral nucleophiles. The three methods consist of (1) half-life dependence of k app , (2) sequential linear pseudo-first-order correlation, and (3) revised instantaneous rate constant analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The first, classical approach is individual evaluation of the kinetic curves. Based on this approach, an algorithm has been proposed to determine whether the reaction mechanism is complicated or not. The correct model should not contradict the shape of kinetic curves, the k obs – C X dependence, the stoichiometry of the reaction, or the determined number of reaction components .…”
Section: Resultsmentioning
confidence: 99%
“…The first, classical approach is individual evaluation of the kinetic curves. Based on this approach, an algorithm has been proposed to determine whether the reaction mechanism is complicated or not. The correct model should not contradict the shape of kinetic curves, the k obs – C X dependence, the stoichiometry of the reaction, or the determined number of reaction components .…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, we found that, at reaction temperatures below 308 K, we could not observe any deviations from simple first-order kinetics. Since that time our non-steady-state kinetic methods have continually developed and been improved significantly. Due to the negative critique of our mechanism and the incomplete nature of our experimental study, the data that this paper is based on were obtained using our most recently developed kinetic techniques. …”
Section: Resultsmentioning
confidence: 99%
“…Instantaneous rate constant (IRC) analysis , of the reactions between MAH/MAH- d 2 and BQCN + in AN is illustrated by the plots in Figure . An important feature of the plots in Figure is that the experimental data for these figures was the increase in absorbance at 440 nm.…”
Section: Resultsmentioning
confidence: 99%